Problem-Based Learning in Pancasila and Civic Education and Its Implications on Students’ National Character - Syarifatul Fitri Hidayah; Herman Khunaivi (Program Studi PGMI UIN Salatiga, 2022)
This work attempted to document the implementation of problem-based learning in Pancasila and Civic education subject and its implication on the character of Islamic elementary school student. To this end, descriptive qualitative method was applied. The data were collected through observation, interviews, and documentation. This study demonstrated teachers’ efforts in planning the learning process, preparing lesson plans and tools, and preparing materials relevant to the value of nationalism. Students’ activities included memorizing the Pancasila, understanding the Pancasila values in school and home context, and internalizing the character through regular flag ceremony every Monday and singing “Indonesia Raya” anthem. By applying PBL, teachers have a broader opportunity to draw students’ attention and achieve the learning objectives more easily.